Mycorriha-like structures during in vitro culture of stone pine (Pinus pinea L.). A matter of stress? - Zavattieri, A. (2011)
Dichotomous branching of short lateral roots and the formation of coralloid organs are diagnostic of ectomycorrhizas in many pine species, but the micorrhyzae-like structures found in non mycorrhizated plants of pinus plants show a striking similarity to those of ectomycorrhizas. This phenomenon has been observed previously in other pine species and might be indicative of the long co-evolution of these two kingdoms for millions of years. Therefore, it is possible that in the past mycorrhiza-like structures might have been erroneously assumed as plant-fungi associations.